PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP KETERAMPILAN BERBICARA PADA PEMBELAJARAN BAHASA INDONESIA KELAS V SD DI UPTD SDN 015931 PADANG MAHONDANG - Natalia Glorensa Marbun; Rumiris Lumban Gaol; Ribka Kariani br Sembiring; Patri Janson Silaban; Anton Sitepu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the effect of the Role Playing model on students’ speaking skillsin class V. The research model is quantitative using descriptive methods. The research population was class V students at SDN 015931 Padang Mahondang, totaling 30 students. Samples were taken using Random Sampling techniques and were obtained from class V, totaling 30 students. The results of this research show that students’ speaking skills are in the very good category with 77,8. The results of this research show that correlation test shows that the correlation coefficient is rcount (0,953) rtable (0,361), so ha is accepted. So there is an influence of the role playing model on speaking skills on class V at SDN 015931 Padang Mahondang. It can also be seen from the t-test where tcount ttable is 16,633 2,042, this stating that ha is accepted. This shows that there is a significant positive influence from the use of the role playing model on speaking skills in class V Indonesian Language learning at UPTD SDN 015931 Padang Mahondang academic year 2024/2025.